The experience of primiparous mothers in the breastfeeding process - Yayat Suryati; Risda Ramdaniati; Murtiningsih (STIKep PPNI Jawa Barat, 2021)
Aim; to explore how the experience of primiparous mothers in the process of breastfeeding their babies. Design: This study used a literature review research design. Methods: Through the steps in PRISMA, search media using google schoolar, pubmed, science direct and a collection of online journals, the keywords used are primiparous mothers, breastfeeding, primiparas, primipareos. The four journals produced were then analyzed and looked for their relationship. Results: From four studies conducted by Karen P. Jagiello, Ilana R & Azulay Chertok (2015); Yan Zhang, Yi Jind, Carel Vereijken, Bernd Stahl & Hong Jiang (2018); Dwi Margareta Andini, Andari Wuri Astuti & Fitria Siswi Utami (2019) and Juan Wen, Guiling Yu, Yan Kong, Furong Liu, Holly Wei (2020) all stated that the mother's knowledge and support as well as the motivation of the family and medical personnel were also due to the mother's commitment. The key to a mother's success is breastfeeding her baby.